The improvement effect and mechanism of traditional Chinese medicine on chemotherapy-induced diarrhea: a systematic review - Wu, Yuzheng; Cao, Xiaoyan; Yu, Lequan; Yao, Jingchun; Sun, Chenghong; Ruan, Jingya; Wang, Dan; Zhang, Yi; Wang, Tao (Frontiers in Pharmacology, 2026)
Chemotherapy-induced diarrhea (CID) is one of the gastrointestinal adverse effects in cancer patients after chemotherapy, which seriously affects the course of chemotherapy and reduces the survival rate of patients. The medications commonly used to improve CID include loperamide and octreotide. However, the use of these drugs is often accompanied by adverse effects. Currently, extensive preclinical and clinical studies have demonstrated that specific Traditional Chinese Medicine (TCM) formulations and their active metabolites can effectively alleviate CID. Meanwhile, it has been verified that TCM demonstrates favorable curative outcomes and satisfactory safety, which provides a new alternative for patients suffering from this condition. In this review, we focus on the recent studies in which TCM were applied to treat CID both in animal models and patients, and summarize the mechanism of TCM in improving CID from the aspects of antioxidant, anti-inflammation, maintenance of intestinal mucosal barrier and regulation of intestinal flora. We found that TCM has a definite therapeutic effect in the treatment of CID, which reflected in multiple levels and multiple pathways, including Keap1/Nrf2, TLR4/NLRP3, TLR4/NF-κB, JAK2/STAT3, Wnt, AKT, and MAPK. The aim of this review was to provide some references for applying TCM to treat CID in clinic, and provide new insights into the critical path ahead of the development of innovative drugs in alleviating CID.